Aktivitas Gastroprotektif Infusa Serai Wangi terhadap Gastritis Akut pada Tikus Sprague dawley - Nabilah, Avida Shahnaz; Handharyani, Ekowati; Sutardi, Lina Noviyanti; Mustika, Aulia Andi (Acta VETERINARIA Indonesiana, 2024)
Gastritis is an inflammation of the stomach mucosal lining. Citronella grass (Cymbopogon nardus) is a plant that has been used in traditional medicine to treat diseases, including digestive problems. This study aimed to analyze the gastroprotective activity of citronella grass infusion on acidified ethanol-induced gastritis in Sprague Dawley rats. The study was conducted on four groups of rats that were previously fasted for 18 hours. All rats were given treatments: water (HCl/ethanol group), omeprazole (omeprazole group), 20% citronella grass infusion (P1), and 40% citronella grass infusion (P2). After 90 minutes, all groups were administered HCl and ethanol mixture orally and then sacrificed 90 minutes later. The stomachs were collected for gastric fluid pH measurement and macroscopic and microscopic analysis. The results of phytochemical screenings showed that the citronella grass infusion contains alkaloids, flavonoids, saponins, and tannins. The pH values and the gastric lesion scores of P1 and P2 were significantly different (P<0.05) with higher and lower values respectively than the HCl/ethanol group. Macroscopic and microscopic examinations also showed a decrease in gastric lesions in the P1 and P2 groups. These findings confirm the gastroprotective activity of citronella plant infusion. There was no significant difference (P>0.05) between the P1 and P2.